Tren Prevalensi Berat Badan Rendah, Berat Badan Berlebih, dan Obesitas pada Kelompok Dewasa Muda: 1993 – 2014 - Defi Amalia Setia Ningrum; Krisnawati Bantas (Jurnal Ilmu dan Teknologi Kesehatan, 2019)
Worsening nutritional status is the major determinant health problems worldwide, especially in developing countries. Worsening nutritional status at a young age is a strong predictor of the deterioration of health in the elderly. This study aims to estimate the prevalence and assess trends of underweight, overweight, and obesity between 1993–2014 among Indonesian Young Adult. A secondary data from Indonesia Family Life Survey (IFLS) period I (1993) to V (2014) We evaluated trends by using chi-square test to analyze the prevalence ratios (PR) of underweight, overweight, and obesity in each period comparing with the first IFLS study in 1993. The results of this study showed that the highest prevalence of overweight and obesity was in 2014, 23.8% and 8%. The trend of prevalence of underweight likely to be stable in men and decreases in women. The prevalence of overweight and obesity Indonesian young adult both men and women shows an increasing trendency. Results of the calculation of the prevalence ratio showed increasing significantly in both overweight and obesity in 2007 (PR overweight = 1.76 (95% CI: 1.64 - 1.89); PR obesity = 3.00 (95% CI: 2.46 - 3.69)) and 2014 (PR overweight = 2.26 (95% CI: 1.97 - 2.60); obesity PR = 4.73 (95% CI: 3.87 - 5.78)). Management of underweight, overweight, and obesity in young adult is required to prevent obesity and worsening health in adulthood.